(untitled) (International Journal of Food and Nutritional Sciences, 2022)
When India’s population reaches above 1.2 billion and continues to grow at its current pace, there will be a significant food crisis in 25 to 30 years, necessitating the expansion of agriculture. Implementing the proper operational choice at the right time is essential for production farming profitability based on the circumstances at hand and past performance. Precision agriculture is a systematic procedure created to increase agricultural output by precisely adjusting crop and soil management to each field’s unique needs while maintaining ecological integrity. In order to electronically assess the external factors in an agricultural field, this present review focuses on the construction of an automated or Internet of Things (IoT) based irrigation system using portable wireless sensor systems as well as decision analysis techniques. The primary objective of this review is to create a microcontroller system that continuously waters plants and communicates that data to the farmers. Irrigation is a traditional method that uses a larger proportion of laborers than other everyday agricultural practices. Sensors and microcontrollers may be used to autonomously water plants by detecting when they need to be irrigated. Automation entails accelerating production, cutting costs, and making efficient use of resources in coming days. The greatest way to prevent water problems in agriculture will be to use smart irrigation.